Moral sensitivity components identified among nurses from Intensive Care Units - Cláudia Denise Schallenberger; Jamila Geri Tomaschewski-Barlem; Edison Luiz Devos Barlem; Laurelize Pereira Rocha; Graziele de Lima Dalmolin; Liliane Alves Pereira
ABSTRACT Objective: to identify ethical problems from the components of moral sensitivity among nurses of Intensive Care Units. Method: qualitative, exploratory-descriptive study developed in a hospital in the South of Brazil with 19 nurses working in intensive care units through semi-structured interviews that were analyzed through discursive textual analysis. Results: ethical education, dialogue, relationships with other health team members, professional autonomy, knowledge, personal values, effective communication, leadership and patients' positive outcomes were identified as important components of nurses' moral sensitivity, and comprise the domains of moral consciousness, benevolent motivation, and spontaneous moral perception. Final considerations: the components of moral sensitivity identified in this study facilitate nurses' instrumentalization in the face of decision making and ethical problems in the intensive care setting.